The Influence of Dividend Policy and Corporate Social Responsibility on Company Values - Ni Kadek Piora Puspita; I Dewa Nyoman Badera (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2026)
The company value is a crucial aspect that needs to be considered because it reflects the company's performance, which can influence investors' perceptions of the company. This study aims to investigate the impact of dividend policy and corporate social responsibility on company value, using the company's age as a control variable. The study was conducted on all listed companies on the Indonesia Stock Exchange from 2019 to 2022. The sampling method used was purposive sampling, resulting in 112 observational data samples. The analysis technique used in this study was multiple linear regression, assisted by SPSS software. The study's results show that dividend policy and corporate social responsibility have a positive impact on company value.